Revolutionizing Education: Exploring the Impact of Innovative Teaching Methods - Rina Setiawan (Innovative Journal of Educational Research and Insights, 2024)
This study explores the effectiveness of constructivist and traditional approaches in teaching Arabic to beginners. The constructivist approach, grounded in active learning and real-world application, emphasizes learner engagement and collaborative learning. The traditional approach, however, focuses on structured grammar-based instruction, providing learners with a foundational understanding of language rules. Through a comparative analysis of two groups of beginners—one taught using a constructivist approach and the other using a traditional method—the research examines differences in engagement, motivation, and skill development (speaking, listening, reading, writing).